Hot topic 1 - Pavlik, Cheryl
Hot Topics is guaranteed to engage readers, stimulate thinking, and provoke conversation while developing vocabulary and reading skills. The controversial topics explored in the text all have more than one side to them, thus encouraging debate and classroom interaction